Internal vs. Occupational Labour Market - A Neglected Dimension of Hungary's Post-Socialist Transformation - Istvan R. Gabor (Hungarian Academy of Sciences, Institute of Economics, Labour Research Department, 1998)
As a result of the economic transformation that followed the systemic change of the political order, the formerly prominent role of internal labour markets of large enterprises has been largely discontinued in Hungary and taken over by occupational type labour markets. At the same time the Hungarian labour market has become conspicuously closed and inflexible. Looking for the causes of this paradoxical situation the author calls attention to the fact that parallel to the dissolution of the earlier internal labour markets a new institutional infrastructure fitting the logic of operation of occupational type labour markets has as yet failed to evolve.
Keywords: 330